Co-Production Related To Business Counselling in the Microfinance Sector as a Demonstration of Social Cooperation: An Interpersonal Relationship Approach - Abeysekera, Ruwan (My University, 2020)
Microfinance Institutions (MFIs) provide services such as microcredit, savings, insurance and Business Development Services (BDS) to low income people in order to start new businesses and expand existing businesses. MFIs cater to micro enterprises. A microenterprise is defined as an owner-managed business that has fewer than 10 employees. The studies show that micro enterprises not only need micro credit, but also BDS in order to grow their businesses. This study focuses on BDS. BDS are non-financial services such as management training, vocational training skills, marketing assistance and technology access provided to owner managers by MFIs. MFIs could provide BDS to owner managers/clients using business counselling. A good relationship between the counsellor and the client can be considered a defining feature of any successful counselling intervention. This interpersonal relationship enhances co-production of BDS in counselling. Therein, the objectives of this study are; to identify the factors that enhance the interpersonal relationship between the counsellor and the client in microfinance settings that result in enhanced co-production, to identify how interpersonal relationships enhance co-production, and to understand how organisational factors affect interpersonal relationships. The multiple case study method was used to conduct the study and six (6) Sri Lankan Microfinance Institutions (MFIs) were chosen as cases and data was collected by holding in depth interviews. Findings show that factors such as the expertise of the counsellors, social interaction, similar attitudes, intensity of contacts, and power distance influence the relationship between the counsellors and the clients. As a result of the enhanced interpersonal relationships between counsellor and client, parties exchange personal and communal favours thereby further enhancing co-production as well as improving the provision of information by clients. The findings further reveal that interpersonal relationships could be affected by the organisational factors such as the type of MFI and type of linkages. Therefore, the findings of this study will enable MFIs to improve the counselling intervention and will further contribute to the microfinance knowledge and practice domains.
Keywords: interpersonal relationship, co-production, counselling, microfinance, business development services (BDS)